The Engagement-Trust Paradox: A Qualitative Analysis of Baho Gamira’s TikTok Content Among University Students: - Jacqueline Laoli; Afore Tahir Harefa; Neni Suryani Gulo; Sharley Grace Mendrofa (Jurnal Pembelajaran Bahasa dan Sastra, 2026)
This study investigates students' perceptions of promotional content for Baho Gamira Recreational Tourism on TikTok, focusing on the integration of animated storytelling in tourism marketing. Utilizing a qualitative descriptive approach, data were collected through semi-structured interviews and online surveys involving 30 students to analyze the influence of visual narrativity and perceived authenticity on travel intentions. The findings identify a significant "Engagement-Trust Paradox," where creative animation achieved a 100% engagement rate in capturing attention but simultaneously triggered a profound "Trust Gap." Approximately 70% to 90% of participants expressed skepticism regarding the site's physical reality, perceiving animation as a tool that potentially masks logistical deficiencies or exaggerates natural beauty. Furthermore, 75% of respondents felt hindered from visiting due to a critical "Informational Gap" regarding precise location tags, road accessibility, and facility costs. This research concludes that for emerging destinations, creative digital narration must be harmonized with "aesthetic transparency" and factual documentation to convert online engagement into physical visits. Practically, the study recommends adopting a hybrid content strategy that integrates User-Generated Content (UGC) and real-life footage to bridge the gap between digital inspiration and logistical reality, ensuring that the visual "vibe" is supported by verifiable facts to reduce the perceived risk for potential visitors. Keywords: TikTok Marketing, Animated Storytelling, Student Perception, Digital Tourism, Trust Gap.